Empowering Modern Kartinis to Welcome Industry 4.0 through an E-Commerce Workshop - Wina Permana Sari; Hanugra Aulia Sidharta; Sidharta Sidharta (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2022)
Most Indonesians have a strong view that a woman should stay at home and refrain themselves from having a job. These days as technology makes life easier, this view has been shifting. Women are able to work, even from home. Furthermore, during the COVID19 pandemic, the role of women in helping the family’s economy was greatly inﬂuential. During this pandemic, quite a lot of people have been laid oﬀ due to the government enforcing social distancing policy, which aﬀects companies because customers prefer to stay at home and follow the government’s requests. Due to this situation, the authors provide a solution for Indonesian Kartinis, especially the PKK women in Purwodadi Village, City of Malang who mostly have small businesses, such as making traditional kue basah, tailors, and other crafting businesses. They were forced to stop their businesses in this pandemic, and one of the factors was because they could not utilize advanced technology and market their product online. The solution for this issue is giving guidance and e-commerce training for the PKK women using the Asset Based Community Development (ABCD) method, so E-Commerce in every business will be sustainable and the results of increasing knowledge of this E-Commerce workshop are 83%.